Meta-Analysis the Effects of Hand Washing Behavior Using Soap and Latrine Availability on the Diarrhea Incidence in Children Under Five - Dyah Ayu Fatmawati; Sumardiyono; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Diarrheal disease is a major problem in developing countries, including Indonesia. Apart from being a cause of death, diarrhea is also a major cause of malnutrition and can cause extraordinary events. This study aimed to analyze and estimate the effect of washing hands with soap and availability of latrines on the incidence of diarrhea in toddlers, with a meta-analysis based on previous primary studies. Subjects and Method: The meta-analysis was carried out using the PICO format including: (1) Population: Children under five; (2) Intervention: Mother washing hands with soap and having latrines available; (3) Comparison: Mothers who don't wash their hands with soap and don't have latrines available; and (4) Outcome: Incidence of diarrhea. Article searches were performed using several databases such as PubMed, Google Scholar, ScienceDirect, BioMed Central, and PLOS ONE. The keywords used are “Hand Washing OR Hand Hygiene AND “Latrine OR Latrine Availability” AND “Infection” AND “Diarrhea Childhood” AND “Children”. The inclusion criteria for the included articles were full text articles with a cross-sectional design, published years from 2013 to 2022. This study was conducted according to PRISMA guidelines (Preferred Reporting Item for Systematic Reviews and Meta-Analysis). Data were analyzed using the Review Manager 5.3 application. Results: A total of 14 cross-sectional studies were included in this meta-analysis study which contained a total of 12,851 children under five who were at risk of diarrhea. This research article comes from Ethiopia which is on the African continent. The results of this meta-analysis show that mothers who wash their hands with soap can reduce the incidence of diarrhea in toddlers by 0.31 times compared to mothers who do not wash their hands with soap (aOR= 0.31; 95% CI= 0.17 to 0.57; p= 0.001), and the availability of latrines can reduce the incidence of diarrhea in toddlers by 0.38 times compared to the unavailability of latrines (aOR= 0.38; 95% CI= 0.15 to 0.96; p= 0.040). Conclusion: The behavior of washing hands with soap and the availability of latrines can reduce the incidence of diarrhea in toddlers.